Meningkatkan Aktivitas Siswa, Kerjasama, Dan Hasil Belajar Muatan Matematika Menggunakan Model PBL DAN MAKE A Match Di Kelas V SD - Muhammad Sugiyannor; Maimunah (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose of this study is to describe teacher activities, analyze student activities, cooperation, and learning outcomes of mathematical content using Problem Based Learning (PBL) and Make a Match models. This research was carried out using Classroom Action Research (PTK) which was conducted three times. The research setting is in grade V of SDN Kelayan Selatan 3. The types of data in this study are qualitative and quantitative. The results showed an increase in student activity, cooperation, and learning outcomes.